MMTV-NeuT/ATTAC mice: a new model for studying the stromal tumor microenvironment - Yuan, Hongyan (Oncotarget, 2018)
One of the central challenges in cancer prevention is the identification of factors in the tumor microenvironment (TME) that increase susceptibility to tumorigenesis. One such factor is stromal fibrosis, a histopathologic negative prognostic criterion for invasive breast cancer. Since the stromal composition of the breast is largely adipose and fibroblast tissue, it is important to understand how alterations in these tissues affect cancer progression. To address this question, a novel transgenic animal model was developed by crossing MMTV-NeuT mice containing a constitutively active ErbB2 gene into the FAT-ATTAC (fat apoptosis through targeted activation of caspase 8) background, which expresses an inducible caspase 8 fusion protein targeted to mammary adipose tissue. Upon caspase 8 activation, lipoatrophy of the mammary gland results in stromal fibrosis and acceleration of mammary tumor development with an increase in tumor multiplicity. Fibrosis was accompanied by an increase in collagen deposition, α-smooth muscle actin and CD31 expression in the tumor stroma as well as an increase in PD-L1-positive tumor cells, and infiltration by regulatory T cells, myeloid-derived suppressor cells and tumor-associated macrophages. Gene expression and signal transduction profiling indicated upregulation of pathways associated with cytokine signaling, inflammation and proliferation. This model should be useful for evaluating new therapies that target desmoplasia in the TME associated with invasive cancer.